Studi Desktiptif: Persepsi Mahasiswa Ilmu Forensik terhadap Konsep Cyberstalking - Bahrir, Ainun Jaryah (Universitas Medan Area, 2020)
Cyberstalking is behavior that leads to repeated invasion of one's privacy by electronic mail or computer-based communication with a view to controlling, coercing, intimidating, harassing, or threatening. The purpose of this study is to describe the understanding of forensic science students about the concept of cyberstalking; the object criteria of this study are forensic science students who are still active and have taken cybercrime courses. This research method uses descriptive quantitative. Subjects in this study were obtained through purposive sampling with a total of 36 students. The technique of collecting research data is by distributing closed questionnaires. Research data analysis technique is a descriptive analysis technique, describing data obtained using tables and graphs. The results of this study indicate that forensic science students already have the correct perception of cyberstalking. The majority of students can distinguish statements with indications of cyberstalking and not cyberstalking.